2004
DOI: 10.1016/j.cdp.2004.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B testing among Vietnamese American men

Abstract: Vietnamese American men are over 10 times more likely to be diagnosed with liver cancer than their white counterparts. This health disparity is attributable to high rates of hepatitis B virus (HBV) infection. Our study objective was to examine factors associated with HBV testing among Vietnamese men. A population-based survey was conducted in Seattle. The questionnaire content was guided by an earlier qualitative study and the Health Behavior Framework. The survey was completed by 345 men (response rate: 80%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
123
4
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(141 citation statements)
references
References 33 publications
9
123
4
5
Order By: Relevance
“…Un mayor número de visitas médicas (5,15), la presencia de un control médico en el último tiempo (10,12,21,35,38,39) y contar con prestador de salud habitual (33,40) son predictores de mayor adherencia. Específicamente, se ha descrito que visitar al mismo ginecólogo también se considera como un factor de adherencia importante; esto puede deberse al efecto que genera una mejor relación profesional y un mejor seguimiento de la mujer (10).…”
Section: Determinantes Intermediarios (Tabla Ii)unclassified
“…Un mayor número de visitas médicas (5,15), la presencia de un control médico en el último tiempo (10,12,21,35,38,39) y contar con prestador de salud habitual (33,40) son predictores de mayor adherencia. Específicamente, se ha descrito que visitar al mismo ginecólogo también se considera como un factor de adherencia importante; esto puede deberse al efecto que genera una mejor relación profesional y un mejor seguimiento de la mujer (10).…”
Section: Determinantes Intermediarios (Tabla Ii)unclassified
“…This is suggested by the high HBsAg prevalence in children 7,17,22 and similar prevalence among people of Vietnamese origin living in other countries (Table 1). 16,[24][25][26] However, an age-dependent increase in the HBsAg prevalence has also been reported, suggesting the additional role of the horizontal transmission. 17,22 Hepatitis C. Tables 1 and 2 summarize the prevalence of antihepatitis C virus (HCV) in the general population and in key affected populations.…”
Section: Overview-hepatitis B and C And Hiv Coinfection In Vietnammentioning
confidence: 99%
“…In this study the beliefs including Pap tests decrease the risk of cervical cancer , cervical cancer is curable if detected early, testing is necessary for women who are asymptomatic, sexually inactive, or postmenopausal , concern about pain/discomfort as a barrier to screening; family member(s) and friend(s) had suggested testing (social support); doctor(s) had recommended testing communication with health care providers were explored as predictor variables for obtaining pap smear (Taylor VM, 2004). In a multivariate analysis, this study showed being married, knowing Pap testing is necessary for asymptomatic women, doctor(s) had recommended testing, and had asked doctor(s) for testing were independently associated with screening participation (Taylor et al, 2004) . Fear, embarrassment, and cost were more likely to be barrier to adherence cervical cancer screening recommendation among Asian women compared to white women ( Ross, 2008).…”
Section: Other Variablesmentioning
confidence: 99%